2014
DOI: 10.1159/000362409
|View full text |Cite
|
Sign up to set email alerts
|

Death of an Alcohol-Dependent Patient following Intentional Drug Intoxication: Implication of Baclofen?

Abstract: Used in the treatment of spasticity at low doses, baclofen is also prescribed off-label at high doses for the treatment of alcohol dependence. Several cases of baclofen intoxication have been reported, but only 1 case deals with the treatment of alcohol dependence. Thus, we report the first death in the context of baclofen off-label use of an alcohol-dependent patient with a high blood baclofen concentration after intentional drug intoxication. The safety profile of baclofen in the treatment of alcohol depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It has been previously found that beyond 150 or 200 mg of baclofen intake, the severity of intoxication may require that the treatment be carried out in intensive care units ( 32 , 52 ). Moreover, anecdotal reports have suggested that baclofen could be a factor of immediate increased risk for death in case of self-poisoning ( 53 ). However, in this case report, baclofen causality was not explored and many other potential factors could actually explain the death of the patient ( 22 ).…”
Section: Adverse Drug Reactions With Unclear Baclofen Causalitymentioning
confidence: 99%
“…It has been previously found that beyond 150 or 200 mg of baclofen intake, the severity of intoxication may require that the treatment be carried out in intensive care units ( 32 , 52 ). Moreover, anecdotal reports have suggested that baclofen could be a factor of immediate increased risk for death in case of self-poisoning ( 53 ). However, in this case report, baclofen causality was not explored and many other potential factors could actually explain the death of the patient ( 22 ).…”
Section: Adverse Drug Reactions With Unclear Baclofen Causalitymentioning
confidence: 99%
“…However, ingestion of large amounts of baclofen in an attempt to self-arm has been shown to be high-risk. Several reports already insisted on the frequency and severity of baclofen-induced encephalopathy with delirium, seizures, burst suppression on the EEG, leading to mechanical ventilation, aspiration pneumonitis and eventually death [12][13][14][15][16]. Rate of intubation and mechanical ventilation has been reported up to 40 % in a study [17], which is a strong marker of the frequent severity of intoxication.…”
Section: Discussionmentioning
confidence: 99%